Sleep and protein synthesis-dependent synaptic plasticity: impacts of sleep loss and stress - Grønli, Janne; Soule, Jonathan; Bramham, Clive R. (Frontiers in Behavioral Neuroscience, 2014)
Sleep has been ascribed a critical role in cognitive functioning. Several lines of evidence implicate sleep in the consolidation of synaptic plasticity and long-term memory. Stress disrupts sleep while impairing synaptic plasticity and cognitive performance. Here, we discuss evidence linking sleep to mechanisms of protein synthesis-dependent synaptic plasticity and synaptic scaling. We then consider how disruption of sleep by acute and chronic stress may impair these mechanisms and degrade sleep function.